2023
DOI: 10.1039/d2np00084a
|View full text |Cite
|
Sign up to set email alerts
|

Natural products acting against S. aureus through membrane and cell wall disruption

Abstract: This review article highlights the mechanistic insight of the natural products that directly inhibit the Staphylococcus aureus membrane and its membrane biosynthetic enzymes by targeting membrane-embedded proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 182 publications
(268 reference statements)
0
3
0
Order By: Relevance
“…In bacteria, the cell membrane provides a protective barrier as well as proper permeability and maintains the osmotic pressure within bacteria, which is crucial for the integrity of cell walls. It has been found that when the fatty acids of MRSA decreased, the cell membrane of MRSA was destabilized and destroyed, which further caused cell wall damage . Given the results of fluorescence assays, we performed Gram-staining experiments to examine the effects of compounds n31 and n39 on the cell walls of MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…In bacteria, the cell membrane provides a protective barrier as well as proper permeability and maintains the osmotic pressure within bacteria, which is crucial for the integrity of cell walls. It has been found that when the fatty acids of MRSA decreased, the cell membrane of MRSA was destabilized and destroyed, which further caused cell wall damage . Given the results of fluorescence assays, we performed Gram-staining experiments to examine the effects of compounds n31 and n39 on the cell walls of MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…To better address the challenge of resistance, it is necessary to develop new agents for controlling KBC and discover new drug targets against Psa . Finding novel compounds from structurally diverse biocontrol bacteria and identifying new targets for drug action is a meaningful and challenging task . Fortunately, researchers have shifted their focus from only studying the antagonistic effects of biocontrol bacteria against Psa to also investigating the active compounds they produce .…”
Section: Introductionmentioning
confidence: 99%
“…It can become even more difficult when analyzing compounds that target the cell envelope, since the cell wall and membrane(s) are closely connected, both structurally and functionally. Yet, cell wall synthesis is still the most successful and common clinical antibiotic target, and the cytoplasmic membrane has moved more and more into the spotlight of antibacterial drug discovery ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%